Pelatihan Penerapan Internal Control dan Petty Cash Bagi Siswa SMA Harapan Jaya - Yanti, Yanti; Tobing, Yoan; Anastasia, Pricillia (Transpublika Publisher, 2025)
Education serves as a crucial long-term investment for developing skills and improving quality of life in Indonesia. SMA Harapan Jaya requires particular attention regarding basic accounting education, as interviews with accounting teachers revealed that students receive only fundamental accounting material, lacking knowledge of internal control systems and petty cash accounting. This community service activity aimed to enhance students’ understanding of internal control importance and petty cash accounting systems through available accounting methods. The training employed a three-phase approach: theoretical explanation of internal control and cash management principles, practical problem-solving exercises, and quiz-based feedback assessment. The activity was conducted on-site at SMA Harapan Jaya on Friday, October 17, 2025, from 10:00-11:30 a.m., targeting 29 grade XI-1 students majoring in Mathematics and Sciences. Participants demonstrated strong enthusiasm with excellent interaction throughout the session and achieved satisfactory comprehension of the presented material. The school provided cooperative support by supplying necessary facilities and infrastructure, while quiz and questionnaire results confirmed successful knowledge transfer. The training objectives were successfully achieved, with participants expressing high satisfaction with both the training content and instructional methods. The activity produced three key outputs: an article published in an ISSN journal, intellectual property rights (IPR), and products/prototypes, contributing to educational advancement in accounting education at SMA Harapan Jaya and addressing the identified gap in students’ understanding of internal control systems and petty cash management.